Analysis of the Effects of Tool Wear on Dry Helical Milling of Ti6Al4V Alloy. (2015) - Fernández-Vidal, S.R.; Mayuet, P.; Rivero, A.; Salguero, J.; del Sol, I.; Marcos, M.
Abstract: It is not easy to find papers that contain studies about the holes development in Ti alloys by alternative machining processes such as helical milling. The increased competitiveness and legislative requirements in the aeronautical sector has caused the necessity to develop products and processes seeking the greatest profitability and sustainability, taking as reference the so-called four axes for manufacturing performance: economy, energy, environment and functionality. This work reports on the first results of a study about the influence of cutting speed and feedrate on the hole finishing in the oriented helical dry milling process of alloy Ti-6Al-4V.